GENETIC DIVERSITY OF THE CIGARETTE BEETLE, LASIODERMA SERRICORNE (FABRICIUS), DERIVED FROM MITOCHONDRIAL DNA SEQUENCES - RUKHSANA, K.; SEBASTIAN, C. D. (International Journal of Pharma and Bio Sciences, 2015)
The cigarette beetle, Lasioderma serricorne (Fabricius) is one of the major pests for stored tobacco which is widely distributed in the world. It is a pest of many stored products like spices, pet food, dried flowers etc. This study highlights the DNA barcoding and genetic diversity of the cigarette beetle and in discriminating global phylogeographical variants among the Lasioderma species. From this study, L. serricorne in different phylogeographical areas are in a same clade reveals its common ancestry. Here we report the partial sequence of cytochrome oxidase subunit I gene (COI) of L. serricorne (GenBank Accession No. KM 216269) and its phylogenetic relationship with other related insect species. The COI DNA barcode developed in this study can be used for its accurate identification and phylogeographical analysis.